EMPLOYEE REWARD SYSTEMS IN ORGANIZATIONS - Došenović, Dragana (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2016)
Employee rewarding is one of the activities of human resource management concerning the management of money, goods and services that employees receive from their employer in exchange for their work. Given that a properly designed reward system is one of the conditions for a stable business, successful performance of work activities and the achievement of set objectives in each organization, the basic theme of this paper is the employee reward system, with a special focus on diﬀerent elements of it. The purpose of this paper is to describe the role and significance of the observed system and to draw attention to its role in employee’s motivation. Based on the given analysis many conclusions have been drawn. It has been proved that a properly designed employee reward system has many advantages for the organization, which emphasizes its importance.